Atrial Fibrillation and Depression: A Bibliometric Analysis From 2001 to 2021 - Ai, Yuzhen; Xing, Yaxuan; Yan, Longmei; Ma, Dan; Gao, Anran; Xu, Qiwu; Zhang, Shan; Mao, Ting; Pan, Qiu; Ma, Xiaojuan; Zhang, Jingchun (Frontiers in Cardiovascular Medicine, 2022)
Background The control of diseases related to atrial fibrillation (AF) may reduce the occurrence of AF, delay progression, and reduce complications, which is beneficial to the prevention and treatment of AF. An increasing number of studies have shown that AF is associated with depression. However, to date, there has not been a bibliometric analysis to examine this field systematically. Our study aimed to visualize the publications to determine the hotspots and frontiers in research on AF and depression and provide guidance and reference for further study. Methods Publications about AF and depression between 2001 and 2021 were retrieved from the Web of Science Core Collection (WOSCC) database. CiteSpace 5.8. R1, VOSviewer 1.6.16, and Excel 2019 software tools were used to conduct this bibliometric study. Results In total, 159 articles and reviews were analyzed. The number of publications has been increased sharply since 2018. David D. McManus had the largest number of publications. The most prolific country was the USA with 54 publications but the centrality was <0.1. The most prolific institution was Northeastern University. Three clusters were formed based on keywords: The first cluster was composed of atrial fibrillation, depression, anxiety, symptoms, ablation, and quality of life, et al. The second cluster were risk, prevalence, mortality, heart failure, association, et al. While the third cluster included anticoagulation, impact, stroke, management, warfarin, et al. After 2019, stroke and prediction are the keywords with strongest citation bursts. Conclusion Research on AF and depression is in its infancy. Cooperation and exchanges between countries and institutions must be strengthened in the future. The effect of depression on prevalence and mortality in AF, depression on ablation in AF, and impact of depression on anticoagulation treatment in AF have been the focus of current research. Stroke prevention (including anticoagulant therapy) is the research frontier, which may still be the focus of research in the future.